Writing literary texts. A way for future professionals of Physical Culture - Odalys Martínez-Chibás; Erín Iyamisel López-Orppé; Lizet García-Corona (Universidad de Guantánamo, 2016)
An approach to literary fact from reading students learn to read literally, so that they develop receptive and interpretive skills, which in turn requires a varied cultural knowledge, an analysis of the inner world and the ability to interpret the external reality Based on a special relationship with literary texts. This research aims to improve the process of construction of literary texts in students; Experiences are presented in this sense that have been taken since Literature classes and is exemplified by activities based on literary works.